Memahami Prinsip Ambang Penyakit Serangga dalam Konteks Epizootiologi - F. X. Susilo (Universitas Gadjah Mada, 2000)
Disease phenomena in insect population can be understood through epizootic modeling. In a pathosystem, disease is generated by transmission (ρ) and is decayed by death (μ). Mass incidence and decay of disease depend on the disease threshold density (St*) which inherently possesses three traits. First, if the density of susceptible insects (St) > St* then disease incidence (It) will increase ( ΔIt > 0 ). Second, if St < St*, then It will decrease ( ΔIt < 0 ). Third, if St = St* then there will be no new infection ( ΔIt = 0 ). Threshold density can be determined monocyclically through laboratory bioassays and polycyclically through field observation. The values of μ and ρ, which are the principal components of monocyclic threshold density, may indicate whether the corresponding entomopathogen is the better candidate for microbial insecticide or, otherwise, even better as the biological control agent (natural enemy). Meanwhile, the concept of polycyclic threshold density highlights the importance of incorporation of sampling of infected insects into the existing agro-ecosystem monitoring scheme.